Repeated applications of photodynamic therapy on Candida glabrata biofilms formed in acrylic resin polymerized - de Figueiredo Freitas, Lírian Silva [UNESP]; Rossoni, Rodnei Dennis [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP]; Junqueira, Juliana Campos [UNESP] (Springer Nature, 2017)
Previous studies have been suggested that photodynamic therapy (PDT) can be used as an adjuvant treatment for denture stomatitis. In this study, we evaluated the effects of multiple sessions of PDT on Candida glabrata biofilms in specimens of polymerized acrylic resin formed after 5 days. Subsequently, four applications of PDT were performed on biofilms in 24-h intervals (days 6–9). Also, we evaluated two types of PDT, including application of laser and methylene blue or light-emitting diode (LED) and erythrosine. The control groups were treated with physiological solution. The effects of PDT on biofilm were evaluated after the first and fourth application of PDT. The biofilm analysis was performed by counting the colony-forming units. The results showed that between the days 6 and 9, the biofilms not treated by PDT had an increase of 5.53 to 6.05 log (p = 0.0271). Regarding the treatments, after one application of PDT, the biofilms decreased from 5.53 to 0.89 log. When it was done four applications, the microbial reduction ranged from 6.05 log to 0.11 log. We observed that one application of PDT with laser or LED caused a reduction of 3.36 and 4.64 compared to the control groups, respectively (p = 0.1708). When it was done four applications of PDT, the reductions achieved were 1.57 for laser and 5.94 for LED (p = 0.0001). It was concluded that repeated applications of PDT on C. glabrata biofilms showed higher antimicrobial activity compared to single application. PDT mediated by LED and erythrosine was more efficient than the PDT mediated by laser and methylene blue.
Keywords: Candida glabrata; Denture stomatitis; Laser; LED; Photodynamic therapy; Photosensitizers